Identification of molecular markers for disease resistance genes to Fusarium oxysporum f. sp. cubense in Musa acuminata ssp. malaccensis for marker assisted selection (MAS) - Kayat, Fatimah; Javed, Muhammad Asif; Ho, Yuk Wah; Othman, Rofina Yasmin (Penerbit Universiti Sains Malaysia, 2004)
Fusarium wilt is a serious soil-borne disease and caused considerable loss to the banana export trade(Rutherford, 1999). Four physiological races of FOC have been reported based on their selective pathogenecity in different banana cultivars. Race 1 had been found virulent on Gros Michel (AAA genotype) while Race 2 on Bluggoe (ABB) and Race 3 on Heliconia. Finally, Race 4 attacking the Cavendish cultivars (AAA) and also virulent on Gros Michel and Bluggoe. Numerous disease control such as soil amendment with Ca or organic matter as well as fumigation with methyl bromide but it only provide temporary solution to this problem. Therefore planting disease resistance bananas is the best approach as it is economical, effective and practical in the long run.